2018
DOI: 10.24843/itepa.2018.v07.i02.p05
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Penambahan Karagenan Terhadap Karakteristik Permen Jelly Kulit Anggur Hitam (Vitis Vinifera)

Abstract: This study aims to determine the effect of thecarrageenan on the characteristics of grape skins jelly candy and to find the right carrageenan concentration to produce jelly candy with the best characteristics. The experimental design used was randomized block design by treatment with carrageenan concentration of 1.0%, 1.5%, 2.0%, 2.5%, 3.0% and 3.5%. The treatment was repeated as many as 3 repetitions then obtained 18 units of the experiment, the data obtained from the result research were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
0
5
0
1
Order By: Relevance
“…This intrinsic property of carrageenan is expounded upon in the study by Stevani et al (2019), elucidating its capability to bind and retain water. Aligning with the fi ndings of Fajarini et al (2018), it is established that increased carrageenan content contributes to a discernible sweetness in black grape skin jelly candy (Vitis vinifera).…”
Section: Tastementioning
confidence: 83%
“…This intrinsic property of carrageenan is expounded upon in the study by Stevani et al (2019), elucidating its capability to bind and retain water. Aligning with the fi ndings of Fajarini et al (2018), it is established that increased carrageenan content contributes to a discernible sweetness in black grape skin jelly candy (Vitis vinifera).…”
Section: Tastementioning
confidence: 83%
“…The research results indicate that a lower proportion of carrageenan with a higher proportion of gum arabic results in a lower ash content of pumpkin jelly candy. Fajarini et al (2018) state that the mineral content found in kappa carrageenan contributes to an increase in the ash content of black grape jelly candy. The higher the addition of carrageenan, the higher the ash content of the product because carrageenan comes from seaweed with relatively high mineral content (Isnanda et al, 2016).…”
Section: Ash Contentmentioning
confidence: 96%
“…Higher additions of carrageenan and lower additions of gum arabic tend to provide a stronger sweetness and may overshadow the natural fruit flavor, resulting in less preferred taste for jelly candy with high carrageenan content. Fajarini et al (2018) state that an increase in high carrageenan content produces a strong gel and an excessively sweet taste, fitting for jelly candy. Treatment K3 (carrageenan 3% : 2% gum arabic) obtained the highest taste score, indicating jelly candy at this concentration is most preferred by the panelists.…”
Section: Tastementioning
confidence: 99%
“…Pada penelitian ini, kadar abu permen jelly rumput laut mengalami penurunan seiring dengan bertambahnya penambahan bubur buah kersen. Hal ini diakibatkan kersen mengandung 1140 mg/100 g kadar 62 abu (Gemilang, 2012), kadar abu pada buah kersen lebih sedikit dari rumput laut, kandungan mineral pada rumput laut cukup tinggi (Fajarini et al 2018).…”
Section: Kadar Abuunclassified